SAFE FOOD AND GOOD HYGIENE PRACTICES OF EMPLOYEES IN CONVECTIONAL KITCHENS OF FOOD AND BEVERAGE BUSINESSES: THE CASE OF KASTAMONU - ŞENER, Yasin; ÇILGINOĞLU, Hakkı (New Era Journal of Interdisciplinary Social Studies, 2022)
The study was carried out using the face-to-face interview method with the technique of interviewing participants with cooks working in residential food and beverage establishments operating in Kastamonu and having conventional kitchens. The data of the study prepared using the qualitative research method are made up of cooks aged 30-50 dec reside in Kastamonu and participate in the study voluntarily. According to the research findings, participants' sensitivity to food safety is at a certain level, when it comes to kitchen hygiene, they pay attention to chopping boards, countertops and cabinets, they are constantly in control of cross-contamination, HACCP (Hazard Analysis And Critical Control PointsHazard Analysis and Critical Control Points) is a term that some participants do not know about, although it is not known that they are active in practice, it has been reported that some enterprises are providing hygiene training to newly started personnel and that the Covit19 pandemic process has caused very big changes in food safety and good hygiene practices applied in conventional kitchens.